Correlation between the presence of aortic valve sclerosis and mitral annular calcification and severity of coronary artery disease - Mohammed Mahmoud; Tariq Abdelwadoud Hamed Bakr; Ali Elsharkawi (Wolters Kluwer Medknow Publications, 2020)
Background Despite numerous improvements in risk scoring regarding assessment of severity of coronary artery disease (CAD), there still remain patients distinguished as being low risk who experience CAD events, just as patients regarded high risk who stay free of CAD events. Aim To evaluate whether the presence and severity of aortic valve sclerosis (AVS) and/or mitral annular calcification (MAC) as detected by transthoracic echocardiography could be a predictor for the presence and extent of CAD in patients less than or equal to 65 years Patients and methods The study included 80 patients with suspected CAD, referred for coronary angiography for assessment of chest discomfort between January 2015 and April 2017. The patients were divided into two primary groups: group I included 20 patients with ordinary aortic and mitral valve, and group II included 60 patients with AVS and/or MAC. The group II was additionally subdivided into group IIa, comprising 30 patients with AVS, and group IIb, comprising 30 patients with AVS and MAC. The following was accomplished for all groups: detailed clinical history taking, total general and cardiovascular assessment, full laboratory data, 12-lead resting ECG, complete transthoracic echocardiographic assessment, and coronary angiography. Results In the correlation between group I and group II with respect to number of vessels affected, there was an extremely high statistically significant difference between both groups. There was a high statistically significant positive correlation between the sum of aortic valve cusp thickness and severity of CAD evaluated by vessel score in group IIa. Among group IIb, there was a high significant positive correlation between MAC and severity of CAD assessed by vessel score. Conclusions AVS is firmly interrelated with the coronary angiographic Friesinger score to yield a proportion of the degree and of severity of CAD. There is a positive correlation between MAC severity and CAD. Echocardiographically detected MAC can be an indicator of significant CAD.